Central African Republic : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waivers of Nonobservance and Modification of Performance Criteria, Request for Interim Assistance Under the Enhanced Heavily Indebted Poor Countries Initiative, and Financing Assurances Review-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Central African Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This report examines the Central African Republic's Third Review under the Three-Year Arrangement under the Poverty Reduction and Growth Facility and request for waivers of Nonobservance and Modification of Performance Criteria. Global food price hikes and fuel price volatility jeopardize growth, inflation, and the balance of payments. Fiscal performance has been as expected, and all quantitative performance criteria (PC) have been met except for the PC on external arrears and on net credit from commercial banks. Demand for timber has declined, and the unstable domestic security situation has reduced diamond exports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet